Green in the heart or greens in the wallet? The spatial uptake of small-scale renewable technologies. (March 2017) - Allan, Grant J.; McIntyre, Stuart G.
Abstract: The introduction of a Feed-in-Tariff (FIT) support mechanism has spurred development of small-scale domestic renewable electricity generation throughout Great Britain (GB), however the spatial pattern of uptake has been uneven, suggesting that local, as well as between neighbourhood, factors may be at important. As well as confirming that local socio-economic factors, including wealth, housing type and population density are found to be important in explaining uptake of this policy, local "green" attitudes – measured in three different ways – are shown not to be important. Existing local technical expertise, proxied for using data on small-scale renewable electricity devices in each area prior to the introduction of FIT, is an important factor in explaining subsequent adoption. Critically, we also find that there are spatial (i.e. between neighbourhood) processes explaining the uptake of these technologies. Taken together, our results suggest that, as currently designed, FIT policy may be regressive in income and could exacerbate spatial economic inequalities. Abstract : Highlights: First examination of uptake of renewable capacity under the UK's Feed-In Tariff. Analyse socio-economic and environmental factors as well as spatial processes. Wealth, population density, property type & existing capacity affect local FIT uptake. Spatial process confirms effects between neighbourhoods, neglected in current policy Highlights.